Size controlled synthesis of starch nanoparticles by a simple nanoprecipitation method - Chin, Suk Fun; Pang, Suh Cem; Tay, Soon Hiang Tay (Elsevier, 2011)
Starch nanoparticles of particle size range between 300 nm and 400 nm were synthesized by a simple nanoprecipitation method from native sago starch (Metroxylon sagu). Starch nanoparticles were formed by controlled precipitation through drop-wise addition of dissolved native starch solution to excess absolute ethanol. The size and shape of starch nanoparticles were modulated varying the synthesis parameters including the use of appropriate surfactant. Starch nanoparticles with mean diameter of about 150 nm were obtained in the presence of surfactants during precipitation. Both solvent and non-solvent systems used in the synthesis method were aqueous-based and the method was facile, and easy to perform as compared to other synthesis approaches previously reported.